Shashṭha Jātīẏa Cārkalā Pradarśanī = Sixth National Art Exhibition (Samakālīna Bāṃlādeśa śilpakalā sirija, 1982)
Reproduction of the paintings, terracottas, and wood-cuts by contemporary Bengali artists.